Patterns of strategy development - Bailey, Andy; Johnson, Gerry (Cranfield University, 1996)
This paper builds on a multidimensional framework of strategy development to more clearly understand the processes by which strategy develops within organisations. It reports on a survey based research project which employs senior executives’ perceptions of the strategy development process in their organisations to examine how context specific configurations of dimensions explaining such processes can advance our understanding of strategic management. Six configurations are identified as commonly occurring and are seen to be associated with contextual variables at an organisational and industry level.
Keywords: Strategy development; Organisational configurations; Multidimensional process